The Nature Of Caretaker Speech In Disciplining Children Found In The Finck Family In Nanny 911 Reality Show Episode 1 And Its Implication In English Teaching To Young Learners - Wati, Asri Heru; , Prof. Dr. Endang Fauziati; , Dr. Mauly Halwat (2015)
This study is mainly intended to find out the nature of caretaker speech found in the Finck Family Found in Nanny 911 Reality Show Episode 1. The objectives of this research are to analyze type of language form, analyze type of language function, and message contained in caretaker speech found in Nanny 911 Reality Show Episode 1. This study is qualitative research which involves approach analysis. The objectives of this research are to analyze the type of language form, and to analyze the type of language function, and to analyze the message function in the Finck Family found in Nanny 911 reality show episode 1. In collecting the data, the researcher uses documentation expert. The data are analyzed using Huberman and Miles theory. The study in this research, the caretaker uses expression more than sentence for example "reward for good behavior" and "simple word". The result showed that there are 7 form of expressions, 8 form of type sentences divided 2 classifications which the highest of expression is 32,35% about logical consequences and the highest of sentence is 11,54% about imperative sentence. Considering the result above, it can be concluded that caretaker speech is good choice to controlling or disciplining children.